Perancangan Aplikasi Point Of Sale Pada Toko Kang Udin Berbasis Web - Bhakti Hanggoro; Fitri Yanti (CV. Multi Kreasi Media, 2023)
In conducting sales transaction activities, recording goods and reporting sales transactions, Kang Udin Store is still done conventionally by handwriting. Difficulties in recording stock data of incoming goods and outgoing goods, as well as transaction calculations cause inaccurate data. In making a report is very time consuming because it has to find and collect the necessary data from the records in the report book. This can lead to human errors. Therefore, researchers built the Point of Sale (POS) application at Kang Udin Store is built using the waterfall method.The design of this POS application uses Unified Modeling Language (UML) to describe the processes that occur in the POS system. The diagrams used are use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The programming languages used are PHP with codeigtniter framework, and MySQL as a database. The results of this Point of Sale application design make it easier for Kang Udin Stores to manage sales transactions, manage stock data and recapitulate sales transaction reports.